2014
DOI: 10.1080/10286020.2014.960857
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive constituents of oleanane-type triterpene saponins from the roots ofGlycyrrhiza glabra

Abstract: Three new oleanane-type triterpene saponins, namely licorice-saponin M3 (1), licorice-saponin N4 (2), and licorice-saponin O4 (3), an artificial product (4), as well as five known triterpene glucuronides (5-9), were isolated from the roots of Glycyrrhiza glabra L. Their structures were established using 1D and 2D NMR spectroscopy, mass spectrometry, and by comparison with spectroscopic data reported in the literature. The inhibitory effects of the selected compounds on neuraminidase were evaluated, and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The configuration of the sugars of compounds 1 and 3 was determined by acid hydrolysis and GC experiments based of the literature procedure [ 6 , 9 ]. The specific steps were as follows: a solution of compounds 1–3 (1.0 mg each) in 1 N HCl (1 mL) was stirred at 90 °C for 2 h. After cooling, the solution was evaporated under a stream of N 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The configuration of the sugars of compounds 1 and 3 was determined by acid hydrolysis and GC experiments based of the literature procedure [ 6 , 9 ]. The specific steps were as follows: a solution of compounds 1–3 (1.0 mg each) in 1 N HCl (1 mL) was stirred at 90 °C for 2 h. After cooling, the solution was evaporated under a stream of N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Phytochemical studies have showed that triterpenoid saponins and flavonoids were the two of major kinds of active substances of Glycyrrhiza , which have a variety of pharmacological activities, including hepatoprotective [ 1 , 2 ], antiviral [ 3 ], anti-inflammatory [ 4 ] and antioxidative [ 5 ] effects. Recently, we reported the chemical constituents of G. uralensis and G. glabra , as well as their cytotoxic or neuraminidase bioactivities [ 6 , 7 ]. As part of our ongoing research on the genus Glycyrrhiza , an extensive phytochemical investigation on the roots of G. inflata has now led to the isolation of two new oleanane-type saponins 1 , 3 and nine known saponins 2 , 4–11 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, similar triterpene saponins, such as licorice-saponin G2 (9) and araboglycyrrhizin (16), were also observed in G. uralensis, G. glabra, and G. inflate. Eleven triterpene saponins (2, 4, 5, 10-12, 14, 25, 26, 36, and 41) were also found both in G. uralensis and G. glabra, including uralsaponin B (2) [16,21], licorice-saponin B2 (4) [22,23], licorice-saponin C2 (5) [22,23], licorice-saponin H2 (10) [23,24], licorice-saponin J2 (11) [23,24], licorice-saponin K2 (12) [21,24], 18α-glycyrrhizic acid (14) [17], licorice-saponin M3 or uralsaponin T (25) [27,31], licorice-saponin N4 (26) [31,32], uralsaponin V (36) [21,27], and 3-O-β-d-glucuronopyranosylglycyrrhetinic acid (41) [21,27].…”
Section: Hepatoprotective Activitiesmentioning
confidence: 97%
“…Oleanolic acid (3b-hydroxy-olea-12-en-28-oic acid, OA) has been isolated from several plants, including Olea europaea L. , Glycyrrhiza sp. , Forsythia suspensa , Dendrobium sp ., and other plants [ 2 , 3 ]. A pentacyclic triterpenoid compound, OA has been used in hepatitis and cirrhosis patients for over 20 years in China because of its hepatoprotective effect [ 4 ].…”
Section: Introductionmentioning
confidence: 99%